Implementation of the Kahoot! as an Effort to Improve the Quality of Interactive Physics Learning at SMAN 6 Bengkulu Tengah - Utama, Tiara Hardyanti; Koto, Irwan; Yanti, Fitri April; Lestari, Ladia; Rahmawati, Nurul Ita; Hafishbulla, Irfan (CV Media Inti Teknologi, 2025)
Background of the Study: The incorporation of technology in education has become increasingly vital in the digital age, especially to augment student interest and engagement in physics, a discipline frequently regarded as challenging and uninspiring.Purpose and Scope of the Paper: This community service program seeks to utilize Kahoot! as an interactive digital learning platform to enhance student engagement in physics education at Senior High School 6 (SMAN 6) Bengkulu Tengah.Methods: We implemented the activities using a participatory method, including direct instruction for teachers and interactive Kahoot! sessions with students. The activity encompassed socialization, demonstrations, and practical applications in the educational context.Results: The findings demonstrated that both educators and learners reacted favorably to the implementation of Kahoot! resulting in heightened student’ engagement and a more vibrant classroom environment. Students exhibited enthusiasm, a competitive disposition, and enhanced concentration throughout physics learning sessions.Conclusions: Kahoot! serves as an exciting and effective alternative learning platform that promotes active engagement and improves comprehension of physics subjects. It offers educators a pragmatic instrument to enhance pedagogical approaches in accordance with the traits of the digital generation.